Serum procalcitonin and CRP levels in non-alcoholic fatty liver disease: a case control study - Ersoz Galip; Akarca Ulus S; Yuce Gul; Ozutemiz Omer; Oruc Nevin; Gunsar Fulya; Batur Yucel (BMC Gastroenterology, 2009)
Abstract Background Both C reactive protein (CRP) and procalcitonin (PCT) are well known acute phase reactant proteins. CRP was reported to increase in metabolic syndrome and type-2 diabetes. Similarly altered level of serum PCT was found in chronic liver diseases and cirrhosis. The liver is considered the main source of CRP and a source of PCT, however, the serum PCT and CRP levels in non-alcoholic fatty liver disease (NAFLD) were not compared previously. Therefore we aimed to study the diagnostic and discriminative role of serum PCT and CRP in NAFLD. Methods Fifty NAFLD cases and 50 healthy controls were included to the study. Liver function tests were measured, body mass index was calculated, and insulin resistance was determined by using a homeostasis model assessment (HOMA-IR). Ultrasound evaluation was performed for each subject. Serum CRP was measured with nephalometric method. Serum PCT was measured with Kryptor based system. Results Serum PCT levels were similar in steatohepatitis (n 20) and simple steatosis (n 27) patients, and were not different than the control group (0.06 ± 0.01, 0.04 ± 0.01 versus 0.06 ± 0.01 ng/ml respectively). Serum CRP levels were significantly higher in simple steatosis, and steatohepatitis groups compared to healthy controls (7.5 ± 1.6 and 5.2 ± 2.5 versus 2.9 ± 0.5 mg/dl respectively p < 0.01). CRP could not differentiate steatohepatitis from simple steatosis. Beside, three patients with focal fatty liver disease had normal serum CRP levels. Conclusion Serum PCT was within normal ranges in patients with simple steatosis or steatohepatitis and has no diagnostic value. Serum CRP level was increased in NAFLD compared to controls. CRP can be used as an additional marker for diagnosis of NAFLD but it has no value in discrimination of steatohepatitis from simple steatosis.